Reconstructing the International Institutional Order Inaugural Lecture delivered on Thursday 3 December 2020 - Besson, Samantha (Leçons inaugurales, 2021)
States are no longer alone on the international scene. Other institutions intervene alongside States, and even sometimes in their place, such as international organizations, multinational corporations, non-governmental organizations, regions or global cities. Still, one would look in vain for clear indications in international law, including for the basic principles of an "international law of institutions" that could address the three fundamental questions of social and political organization that are representation, regulation and responsibility. What institutions may act in whose name internationally? What are the conditions for their actions to bind us legally and have the legitimacy to do so? And what institutions should be held responsible, by whom and how, in case of violation of international law? The time has come to reconstruct the international institutional order.